THE MOTIVATION OF READING AND WRITING AND THE DIFFICULTIES FOR THE DEVELOPMENT OF THE EDUCATOR - Silva Monteiro Gonçalves, Denilza; de Fátima Marinho Teodoro, Maria; de Jesus de Oliveira Fernandes, Maria (Revista Gênero e Interdisciplinaridade, 2023)
In this article, we seek to reflect the importance of motivation in reading and writing in the student’s development. Motivational processes have been the focus of studies in the area of education, as they are considered one of the factors that favor learning, the teacher is part of this process and of school dynamics as a mediator in the classroom. A survey of national articles published on the topic was carried out in the main Scielo and Revistas de Psicopedagogia databases. Learning Difficulties regarding reading and writing are frequent in schools, especially in the initial grades of elementary school. It is a term that draws attention to the existence of children who attend school and who present various types of difficulties, although they do not present no type of physical, sensory, intellectual or emotional defects. The research carried out allows us to conclude that the relationship between learning goes beyond any established precondition, it is reciprocal and, in this way, motivation can have an effect on learning and performance, just as learning can interfere with motivation. This article seeks to highlight the importance of motivation in the learning processes and student success in the school context. We conclude that reading and writing play an important role in the student’s life and that from it, the student will develop a critical view of the world, enabling greater and better interaction in the context in which they are inserted.